Characterization of Iron Removal Process Products from Atmospheric Lateritic Ore Leaching Solution by using 20 and 25% of Calcium Carbonate - Muhammad Nibras Azza Adhikara; Reza Miftahul Ulum; Alfian Ferdiansyah Madsuha; Faizinal Abidin (Jurnal Metal Indonesia, 2021)
AbstractElectric vehicles become the alternative to solve the climate change and global warming problems by providing a more eco-friendly and sustainable source of energy. As the demand for sustainable vehicles increased, the functionality of batteries become crucial. One of the important aspects inside the batteries is nickel. Nickel plays a big role in lithium-ion batteries by delivering greater amounts of energy density with a higher storage capacity, which means it provides bigger efficiency to the batteries. Yet, the attempt of optimizing nickel extraction remains a challenge. Therfore, nickel extraction process of lateritic ore with high efficiency is investigated by using hydrometellurgy process, specifically the iron removal process in atmospheric condition in mixed hydroxide precipitates (MHP) route.The reagent solution of (20% w/w and 25%  w/w) calcium carbonate (CaCO3) at pH (1, 2, 3) were utilized as additive in this process. The precipitates resulted from PLS were characterized by x-ray diffraction (XRD) and Scanning Electron Microscopy - Energy Dispersive X-Ray (SEM–EDS), while the filtrates were investigated by Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Analysis based on precipitates demonstrates that the acid neutralization process took place with a sufficient amount of iron in the precipitates with the least amount of nickel. In addition, all pH and concentration of precipitates qualitatively illustrate the same neutralization process involving calcium and sulfur. From the results of filtrate through ICP testing in this study, pH 1 for both 20% and 25% concentration provides the lowest recovery rate alongside the smallest ppm compare to pH 2 and 3; thus, the iron precipitates in the formation of iron sulfide and/or iron sulfate. Overall, the optimum parameter is 25% of calcium carbonate, pH 1, 90oC for 2 hours of agitation to reduce the amount of iron in the solution.